AB0932 Helicobacter pylori antigen specific antibodies in psoriatic arthritis. (12th June 2018) - Patrikiou, E.; Liaskos, C.; Zafiriou, E.; Efthymiou, G.; Scheper, T.; Meyer, W.; Roussaki-Schulze, A.; Sakkas, L.I.; Bogdanos, D.P.
Abstract : Background: The role of Helicobacter pylori (Hp) infection in the aetiopathogenesis of psoriatic arthritis (PsA) and psoriasis (Ps) is currently inconclusive, as studies reported increased, decreased or comparable to controls frequency of anti-Hp antibodies. Objectives: To test antigen-specific Hp antibodies in a well-defined cohort of PsA patients and demographically matched Ps patients and healthy controls (HCs). Methods: A total of 140 serum samples (48 PsA, 37 Ps and 55 HCs) were tested for anti-Hp antibodies by a western blot immunoassay using whole Hp extract as antigenic source. Results: Overall, anti-Hp seropositivity was similar in PsA (19/48, 39.6%) and Ps (16/37 43.2%, p>0.05) but significantly lower compared to HCs (33/55, 60%, PsA vs HC, p=0.039). Overall, IgG anti-CagA and VacA, the most diagnostically relevant anti-Hp antibodies, were present in 26/48 (54.2%) and 5/48 (10.4%%) PsA patients, respectively, compared to 15/37 (40.5%) (p=ns) and 1/37 (2.7%) (p=ns) Ps respectively, as well as in 39/55 (70.9%), (p=0.079) and 4/55/97.2%) (p=ns) HCs, respectively. Compared to HCs, patients with PsA had higher reactivity to p29 (UreA) (31/48, 64.6% vs 24/55, 43.5%, p=0.033) and to p54 (24/48, 50% vs 15/55, 27.2%, p=0.017) and tended to have higher positivity against p75 antigen (9/48, 18.9% vs 3/55, 5.4%, p=0.062). Reactivity to p50 (15/48, 31.3% vs 50.9, p=0.042) and p33 antigen (3/48, 6.3% vs 10/55, 18.2%, p=0.061) was lower in PsA than in HCs. No differences on anti-Hp antigen specific antibodies was found between PsA and Ps. Conclusions: Although overall reactivity to Hp in PsA and Ps is lower than HCs, Hp infection cannot safely be considered a protecting microbial agent for these diseases, as reactivities to some Hp antigens are more frequently recognised to these diseases than in HCs. Disclosure of Interest: E. Patrikiou: None declared, C. Liaskos: None declared, E. Zafiriou: None declared, G. Efthymiou: None declared, T. Scheper Employee of: EUROIMMUN, W. Meyer Employee of: EUROIMMUN, A. Roussaki-Schulze: None declared, L. Sakkas: None declared, D. Bogdanos: None declared